Regulation, Cross Border Migrants and the Choice of Remittance Channels in South Africa - Akinboade, Oludele Akinloye; Daseman, Anrich; Taft, Trevor; Molobi, Victor M.S. (Journal of Economics and Behavioral Studies, 2017)
Remittances have become an increasingly important factor in developing economies. Among others, compliance with onerous regulation requirements discourages the use of formal methods of remittances. The paper discusses results from a survey of the influence of regulation on the choice of migrants’ remittance channels in South Africa. It aims to highlight how regulation affects the choice between formal and informal channels of remitting funds. A questionnaire was administered to collect primary data from migrants seeking documentations from the Department of Home Affairs, those remitting funds at taxi ranks or bus terminals, and those remitting through commercial banks and money transfer operators. 275 responses were analysed using a Likert rating scale format of 1 (highest) to 5 (lowest). Regulatory requirements of documentary evidence are an important factor influencing the choice of the remittance channel used. Documentation requirement in the formal market causes migrants to be ineligible for the formal channels of remittances and is a factor that influences the choice of remittance channel. Restrictive visa requirements could easily push migrants to become illegal aliens which further deny them access to formal remittance channels. The paper adds to the academic literature on the determinants of remittance channels in Africa. Understanding the relevant issues could assist regulatory authorities to restructure the remittance market with a view to encouraging migrant workers to enter the formal financial system.